Wives, Clerks, and 'Lady Diplomats': The Gendered Politics of Diplomacy and Representation in the U.S. Foreign Service, 1900-1940 - Molly M. Wood (European Journal of American Studies)
In the first few decades of the twentieth century, as the United States asserted itself on the world stage, American women played important roles in the work of diplomacy within the formal U.S. Foreign Service structure. They accompanied their diplomat husbands abroad, as wives and quasi-professional partners in the Service, primarily focusing on the critical social and domestic aspects of diplomatic life abroad.  As these American missions grew in size and complexity during the period from 1900 to 1940, U.S. State Department officials saw the need for additional clerical assistance, and increasingly relied on the work of women, as clerks and stenographers.  As employees of the U.S. State Department, these women also maintained the representative qualities associated with diplomatic work. During this same time period, the U.S. State Department and the Foreign Service in particular remained rather adamantly convinced that American women were “not fitted to discharge the exacting and peculiar duties of a Foreign Service Officer.”  Increasing pressure from women’s groups resulted in a protracted debate over the suitability of women to serve as official representatives of the U.S. government in overseas positions. This paper will analyze the debates, in the State Department and among American diplomats abroad, about the roles of women as wives, clerks and professional diplomats  in the U.S. Foreign Service during the critical pre-World War II era.